Pengaruh Pengungkapan Green Intellectual Capital, Green Accounting, dan Struktur Modal Terhadap Nilai Perusahaan - Putri Adelisa; Sekar Mayangsari (Masyarakat Ekonomi Syariah Bogor, 2025)
This study aims to test and analyze the effect of disclosure of Green Intellectual Capital, Green Accounting, and Capital Structure on Firm Value in the mining industry. This research was conducted using quantitative methods. The data used in this is secondary data. This study uses data from all companies in the mining industry listed on the Indonesia Stock Exchange in 2021-2023 as a population. A total of 63 companies were selected using purposive sampling method. The analysis technique in this study is multiple linear regression analysis. The results of hypothesis testing in this study indicate that Green Intellectual Capital and Green Accounting have negative effect on Firm Value. Then Capital Structure has a positive effect on Firm Value.